DDEL-03. LONG-TERM INTRAVENTRICULAR THERAPY ALTERNATING ETOPOSIDE AND LIPOSOMAL CYTARABINE: EXPERIENCE IN 75 CHILDREN AND ADOLESCENTS WITH MALIGNANT BRAIN TUMORS. (4th December 2020) - Stepien, Natalia; Peyrl, Andreas; Azizi, Amedeo; Gojo, Johannes; Mayr, Lisa; Reisinger, Dominik; Haberler, Christine; Czech, Thomas; Slavc, Irene
Abstract: BACKGROUND: Malignant brain tumors of childhood carry a high risk for leptomeningeal dissemination and tumor cells floating in the CSF are often not amenable to systemic and/or antiangiogenic chemotherapy. We report on our experience with an intraventricular therapy consisting of alternating cycles of liposomal cytarabine and etoposide. PATIENTS AND METHODS: Between 2004 and 2017, 75 patients aged 0.6 to 22 years (median 11) with various malignant brain tumors received intraventricular etoposide 0.25mg (<1year) - 0.5mg on five consecutive days alternating with liposomal cytarabine at a dose of 25mg (<3 years) - 50mg via an Ommaya reservoir. RESULTS: 5533 doses of etoposide (5–277/patient, median 141) corresponding to 1–56 five-day-cycles/patient alternating with 534 doses of liposomal cytarabine (1–21/patient, median 11) were administered. Treatment was given over a period of 1 – 146 months (median 73.5). Toxicities did occur but were infrequent and mostly mild. Since all patients received some sort of concurrent anti-cancer therapy, the efficacy of intrathecal therapy cannot be assessed independently. However, 29/75 patients are still alive, and none of the patients had tumor cells in the CSF at their last evaluation. CONCLUSION: In conclusion, alternating intraventricular liposomal cytarabine and etoposide produced responses and proved to be an important adjunct for patients receiving drugs with a low penetrance into the CSF. Since production of liposomal cytarabine was discontinued in 2017 it remains to be determined whether substitution of the slow release formulation by aqueous cytarabine on days 1, 4, 8, and 11 may produce similar results.